Theories of Corporate Governance: A Legal Analysis - Khitiri, Beka (Journal of Law, 2017)
The purpose of those who rule is to lead the society to a better future, which can only be achieved via the methods and principles of good governance. One of the primary instruments via which good governance occurs in practice, is the adoption of legal acts by the branches of government. However, in order for the laws to have a positive effect on the future of the society, they must be based on solid theoretical bases. In light of the aforesaid, it is quite problmatic that quite often rules are adopted, which are based on theories, that the authors of such laws neglected to study and comprehend in depth. It is imprative that the fundamentals be undestood better for good governance to occur. One of the fields in which there is somewhat of a lack of understanding of the basics in Georgia is that of corporate governance. We can encounter extensive regulation in the field of corporate governance, both on the primary legislative level as well as in secondary legislation, in Georgia. Despite this, there is all but no academic literature available, which would analyze the differring, yet currently accepted theories of corporate governance. It is exactly the filling of this hole and the support for introducing the principles of good governance in the said field that is the primary aim of the research at hand.